Pengaruh Audit Lag, Rasio Leverage, Rasio Arus Kas, Opini Audit Tahun Sebelumnya dan Financial Distress Terhadap Penerimaan Opini Going Concern (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2009-2012) - Safira Pramestri Ibrahim; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence of the influence of audit lag, leverage ratio, operating cash flow, audit opinion prior, and investment to the acceptance of going concern opinion by auditor. Hypothesis (1) audit lag positively affect to the acceptance of going concern opinion, (2) leverage ratio positively affect to the acceptance of going concern opinion, (3) cash flow ratio negatively affect to the acceptance of going concern opinion, (4) prior year audit opinion positively affect to the acceptance of going concern opinion, and (5) financial distress negatively affect to the acceptance of going concern opinion. The reasearch used 122 manufacturing companies listed on Bursa Efek Indonesia (BEI) from 2009-2012. Samples were selected using purposuve sampling method. Data were analyzed by logistic regression analysis.The result shows that the operating cash flow, audit lag, and cash flow ratio don’t have effect to the acceptance of going concern opinion. While prior year audit opinion and financial distress affect to the acceptance of going concern opinion.